2020
DOI: 10.1111/jfpp.14483
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of phenolics, capsaicinoids, antioxidant properties, and major macro‐micro minerals of some hot and sweet peppers and ginger land‐races of Malaysia

Abstract: There are compelling evidences that oxidative stress plays important role in age‐related neurodegenerative diseases and natural food‐derived dietary antioxidants appear to be the first line of defence to take care of the oxidative stress. The analysis results of this study showed that Cili Burung of the hot pepper landraces contained the highest amount of TPC (1.00 mg/g DW), TFC (0.17 mg/g DW), capsaicinoids (0.05 mg/g), and the highest FRAP activity (439 mg/g DW). However, DPPH assay revealed the highest DPPH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
(62 reference statements)
2
6
1
Order By: Relevance
“…Carotene concentration was around 4.2-fold higher in red than in green fruits in most landraces, but this behavior rose between 7.36- and 11.51-fold in three of the 18 landraces (P-39, P-49, P-50). This finding in mature fruits has been reported by several authors in mature fruit, specifically commercialized paprika, and sweet and hot chili peppers [ 32 , 33 , 49 , 50 ] and is related to not only the increment in the number of total carotenoids, but also to the change in the pigment profile [ 4 , 34 ]. During pepper ripening, chloroplast pigments (chlorophylls and carotenoids like lutein and neoxanthin) disappear, while carotenoid chromoplast pigments (β-carotene and xanthophylls like capsanthin) are synthesized [ 34 , 51 , 52 , 53 ].…”
Section: Discussionsupporting
confidence: 82%
“…Carotene concentration was around 4.2-fold higher in red than in green fruits in most landraces, but this behavior rose between 7.36- and 11.51-fold in three of the 18 landraces (P-39, P-49, P-50). This finding in mature fruits has been reported by several authors in mature fruit, specifically commercialized paprika, and sweet and hot chili peppers [ 32 , 33 , 49 , 50 ] and is related to not only the increment in the number of total carotenoids, but also to the change in the pigment profile [ 4 , 34 ]. During pepper ripening, chloroplast pigments (chlorophylls and carotenoids like lutein and neoxanthin) disappear, while carotenoid chromoplast pigments (β-carotene and xanthophylls like capsanthin) are synthesized [ 34 , 51 , 52 , 53 ].…”
Section: Discussionsupporting
confidence: 82%
“…In addition, Martí et al [46] did not find significant changes in the total antioxidant activity between green and red peppers of different cultivars. It should be noted that DPPH and ABTS •+ radical scavenging activity as well as the ferric reducing antioxidant power assay (FRAP) are greatly cultivar-dependent [21,27,43,47,48], which can partially explain the different trends found in the present study as well as in the literature. Concerning the agronomic production system effect on the radical scavenging activity, conventional peppers showed the highest TPC and TEAC but lower DPPH and ABTS •+ activities, compared to organic peppers. )…”
Section: Antioxidant Activity and Total Phenolic Content Of Entinas Sweet Pepperssupporting
confidence: 52%
“…(2019) found that normal hepatic parenchyma was present in the liver of rats treated with 1 ml of 24 mg/ml of aqueous ginger extract for 3 months. Ginger is considered to be a valuable source of antioxidants and to provide the daily diet with macromineral and micromineral nutrients to improve health (Alam et al., 2020).…”
Section: Discussionmentioning
confidence: 99%